NSW/ACT Promoting Excellence Network. - Wilson, Ann; Moore, Natasha (Office for Learning and Teaching, 2014)
The network aims to build on the work of the NSW/ACT PEI network by: further developing the network encouraging/supporting wider institutional participation, further developing the capabilities of the members of the network to exercise leadership within and beyond their institutions in relation to engaging in SoTL, developing, recognising and rewarding quality teaching and disseminating practice, maintaining a variety of for a in which network members can collaborate, share experience, and learn from each other, enhancing awareness of resources and processes developed through the ALTC, and of new activities under the stewardship of DEEWR, and enabling proactive State based engagement with DEEWR by providing a forum for members to engage at the State level with leaders of ALTC projects directly relevant to the work of network members and DEEWR representatives, developing resources the at provide advice and guidelines on the development, implementation and review of institutional strategies to support the recognition and reward of quality teaching.